Mesures objectives et biais d’estime de soi - Jean-Louis Pernin; Jasmine Pernin; Flora Lallau (Communication)
As part of an action research project about changing the name used for fair trade products and about fair trade’s brand capital, the authors examine the methodological impact of the objective measures on subsequent subjective measures presented in their survey. Do the objective measures engender biases regarding the subjective measures?